3D Fast Spin-Echo T1 Black-Blood Imaging for the Diagnosis of Cervical Artery Dissection - Edjlali, M.; Roca, P.; Rabrait, C.; Naggara, O.; Oppenheim, C. (American Journal of Neuroradiology, 2013)
SUMMARY: We performed non-contrast-enhanced 3D fast spin-echo T1 imaging with variable flip angles (CUBE T1) at 3T in 11 patients with CAD. CUBE T1 allowed easy diagnosis of CAD, owing to its comprehensive neck coverage, high spatial resolution enabling multiplanar reformations, fat saturation, and BB effect, the latter also allowing lumen patency to be studied. This sequence may replace 2D axial T1WI for the diagnosis of CAD. BBblack-bloodCADcervical artery dissectionIQRinterquartile range